Effect of lime, organic and inorganic nutrients on wheat (Triticum aestivum)- soybean (Glycine max) cropping system in acidic red soils - S.N. MISHRA; R.K. PAIKARAYAND K.N. MISHRA (Indian Journal of Agronomy, 2001)
A field experiment was canied out during 1988-89, 1989-90 and 1990-92 to study the direct effect of lime, organic and inorgnic nutrients on wheat (Triticum aestivum L. emend. Fiori & Paol.) and its carry-over effect on soybean [Glycine max (L.) Merr.]. Lime (1.25 tonneslha), FYM (4 tonneslha) and boron (10 kglha) in com- bination with 60 kg N + 30 kg P205 20 kg 6OIha resulted in the highest yield of + wheat (29.3 qlha). A significant residual effect was also observed for soybean (23.4 + qlha) with application of 30 kg N + 60 kg P205 30 kg Ø/ha. The direct and the carry-over effects of lime and organic manure along.with inorganic nutrients applica- tion significantly increased the uptake of N, P)and K by both the crops in the cropping system. Key words: Wheat - soybean cropping, Lime, Nutrients, Acidic red soil